"Uma Insólita Experiência: A Arte Dos Grupos Equipe 3 E Arte Ação Na Déc. De 70" - Goncales, Tatiana [UNIFESP] (2018)
During The 70s In Brazil, Under The Military Dictatorship Regime, Two Groups Worked Strongly In The Contemporary Art Scenery Of São Paulo, Equipe 3 (1970-74) And Arte Ação (1974-79), Formed By Lydia Okumura (1948), Genilson Soares (1940) And Francisco Iñarra (1947 - 2009). The Spontaneous And Authentic Way With Which They Developed Their Research, Especially Due To The São Paulo Biennial And Museum Of Contemporary Art (Mac-Usp), Separated Them From The History Of Art In Brazil At The Same Time That Has Brought Them Closer To An Independent And Original Art, Based On The Transgression Of Limits Imposed By The Institution. These Ideas Are Further Developed Through Jacques Rancière's Concept Of "Sharing The Sensitive", And Georges Didi-Huberman's Theory Of Legitimacy Pillars Set By Vasari's History Of Art, As To Understand The Reasons Why The Groups Haven"T Been Considered By This Very History Of Art.